Seismic performance of masonry structures in the rural area during the November 23, 2022, Düzce-Golyaka earthquake - Dedeoglu, Ibrahim Ozgur; Yetkin, Musa; Calayir, Yusuf (Elsevier, 2024)
On November 23, 2022, an earthquake with a magnitude of 5.9 (Mw) w ) occurred, in D & uuml;zce-Golyaka, located in northwestern Turkey. This moderate earthquake, which occurred on the North Anatolian Fault Zone (NAFZ), severely damaged or destroyed many buildings, especially masonry structures, in the rural area. The first part of this study provides information about the tectonic characteristics of the NAFZ's, the seismic characteristics of the earthquake zone, and the main shock. Also, this section compares and evaluates the maximum acceleration and velocity magnitudes from the earthquake records at the acceleration stations in D & uuml;zce province with the seismic values determined for the region in the latest earthquake regulation. Furthermore, the province map visualizes and interprets these values in the form of a density map. The second part of this study presents the effects of the earthquake on masonry structures in rural areas. The damages that occurred to masonry structures are classified and evaluated. It is observed that the primary cause of damage or collapse in masonry structures is the absence of adequate or complete engineering services during their construction, which has led to their non-compliance with current earthquake regulations. Finally, a number of retrofitting techniques are presented which aim to strengthen existing masonry structures with low earthquake performance against future earthquakes, considering the damage classes identified within the study's scope.
Keywords: Masonry structures; Earthquake performance; Damages; North anatolian fault zone; Tectonic characteristics; November 23; 2022; D & uuml;zce-golyaka earthquake